The photoreceptor UVR8 mediates the perception of both UV‐B and UV‐A wavelengths up to 350 nm of sunlight with responsivity moderated by cryptochromes. (24th March 2020) - Rai, Neha; O'Hara, Andrew; Farkas, Daniel; Safronov, Omid; Ratanasopa, Khuanpiroon; Wang, Fang; Lindfors, Anders V.; Jenkins, Gareth I.; Lehto, Tarja; Salojärvi, Jarkko; Brosché, Mikael; Strid, Åke; et al.
Abstract: The photoreceptors UV RESISTANCE LOCUS 8 (UVR8) and CRYPTOCHROMES 1 and 2 (CRYs) play major roles in the perception of UV‐B (280–315 nm) and UV‐A/blue radiation (315–500 nm), respectively. However, it is poorly understood how they function in sunlight. The roles of UVR8 and CRYs were assessed in a factorial experiment with Arabidopsis thaliana wild‐type and photoreceptor mutants exposed to sunlight for 6 or 12 hr under five types of filters with cut‐offs in UV and blue‐light regions. Transcriptome‐wide responses triggered by UV‐B and UV‐A wavelengths shorter than 350 nm (UV‐Asw ) required UVR8 whereas those induced by blue and UV‐A wavelengths longer than 350 nm (UV‐Alw ) required CRYs. UVR8 modulated gene expression in response to blue light while lack of CRYs drastically enhanced gene expression in response to UV‐B and UV‐Asw . These results agree with our estimates of photons absorbed by these photoreceptors in sunlight and with in vitro monomerization of UVR8 by wavelengths up to 335 nm. Motif enrichment analysis predicted complex signaling downstream of UVR8 and CRYs. Our results highlight that it is important to use UV waveband definitions specific to plants' photomorphogenesis as is routinely done in the visible region. Abstract : How UVR8 and cryptochrome photoreceptors function in the natural environment remains poorly understood. We show that transcriptome responses to solar UV‐B and UV‐A below 350 nm (UVsw ) are mediated by UVR8 whereas those induced by blue and UV‐A longer than 350 nm require cryptochromes. UVR8 modulates blue light induced changes in gene expression while cryptochromes antagonize solar UVsw responses mediated by UVR8.